Employee Leadership Emergence and His/Her Own Innovative Behavior: Role-Based Emotional Experience as Mediator - Tianwen Liu; Guangsheng Zhang (Behavioral Sciences)
In the VUCA (which means volatility, uncertainty, complexity, and ambiguity) era, companies increasingly value the emergence of employee leadership as a complement to formal team leadership. Meanwhile, employee innovative behavior, as an important source of firm innovation, has gradually become a key element for the sustainable development of enterprises. Both employee leadership emergence and innovative behavior have significant impacts on the sustainable growth of the employees and companies, yet the relationship between the two has been seldom studied. Whether employee leadership emergence can promote the informal leader’s innovative behavior, thereby achieving the mutual growth of employees and enterprises, has not been tested. Against this backdrop, this study constructs a moderated mediation model from the perspective of leadership role activation to explore the relationship and underlying mechanisms between employee leadership emergence and innovative behavior. By analyzing 304 paired sample data from technology companies in Guangzhou, China, this study finds that employee leadership emergence can influence informal leader’s innovative behavior through the sense of power. Employee self-efficacy strengthens the power perceptions brought about by employee leadership emergence, thus facilitating its positive impact on innovative behavior. This study provides insights into how companies can achieve sustainable growth for both employees and enterprises through employee leadership emergence by revealing the relationship and underlying mechanisms between employee leadership emergence and the informal leader’s innovative behavior.